Storm front - Castle, Richard (Derrick Storm thriller, 2013)
When, throughout the world, high-level bankers are being tortured and murdered by his old nemesis Gregor Derrick, Derrick Storm is called in by the CIA to figure out who Volkov is working for and why, and, with the help of a beautiful and mysterious foreign agent, uncovers a plot that could destroy the global economy.